Membangun Learning Organization Melalui Pendidikan Dan Pelatihan Profesional Berkelanjutan - Timamah, Iik; Listiana, Heni; Jannah, Faridatul; Munawwarah, Faiqatul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Agama Islam Miftahul Ula (STAIM) Kabupaten Nganjuk, Indonesia., 2024)
This article examines the importance of building a learning organization through Continuous Professional Education and Training (PKB) for teachers, with a focus on the challenges faced in the world of modern education. Through the literature review method, the author analyzes various literature to understand how PKB can improve teacher professional qualifications and respond to technological developments and relevant learning demands. The main aim of this research is to show that CPD not only improves teachers' skills and knowledge, but also contributes to the creation of a dynamic and innovative organizational culture. Thus, this article highlights the strategic role of PKB in facilitating positive change in the educational environment, as well as creating a better learning ecosystem for students.